2006
DOI: 10.1073/pnas.0603168103
|View full text |Cite
|
Sign up to set email alerts
|

Functional conservation of cold shock domains in bacteria and higher plants

Abstract: In Escherichia coli, a family of cold shock proteins (CSPs) function as transcription antiterminators or translational enhancers at low temperature by destabilizing RNA secondary structure. A wheat nucleic acid-binding protein (WCSP1) was found to contain a cold shock domain (CSD) bearing high similarity to E. coli cold shock proteins. In the present study, a series of mutations were introduced into WCSP1, and its functionality was investigated by using in vivo and in vitro assays in the context of functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(180 citation statements)
references
References 48 publications
7
168
0
5
Order By: Relevance
“…The expression of CspA and CspB in transgenic rice improved the growth of plants under the effect of a number of abiotic factors like cold, heat and water deficit. The expression of bacterial CSPs increased cold tolerance in transgenic Arabidopsis (Karlson & Imai 2003;Nakaminami et al 2006;Castiglioni et al 2008). Some PR (pathogenrelated) proteins such as PR1, PR2, PR5, PR10, PR11 and PR14 are approved to be up-regulated by low-temperature treatment (Seo et al 2008;Zhang et al 2010).…”
Section: Gene Expression Induction In Response To Low Temperaturementioning
confidence: 99%
“…The expression of CspA and CspB in transgenic rice improved the growth of plants under the effect of a number of abiotic factors like cold, heat and water deficit. The expression of bacterial CSPs increased cold tolerance in transgenic Arabidopsis (Karlson & Imai 2003;Nakaminami et al 2006;Castiglioni et al 2008). Some PR (pathogenrelated) proteins such as PR1, PR2, PR5, PR10, PR11 and PR14 are approved to be up-regulated by low-temperature treatment (Seo et al 2008;Zhang et al 2010).…”
Section: Gene Expression Induction In Response To Low Temperaturementioning
confidence: 99%
“…WCSP1 complements the cold sensitive phenotype of the quadruple Csp-deletion strain of E. coli (BX04), indicating that this protein can function as an RNA chaperone in vivo in a bacterial system (30). Expression studies revealed that some Arabidopsis CSP transcripts are also increased upon cold stress treatment, indicating a potential role in cold adaptation (19,31,32).…”
Section: Functions In Cold Stress Adaptationmentioning
confidence: 95%
“…In the case of plant CSPs, no evidence has been produced to suggest that they may function to directly affect transcription. However, CSPs from wheat and Arabidopsis are localized to the nucleus (30,(32)(33)(34)53), which indirectly supports a putative functional role related to transcription.…”
Section: Transcriptionmentioning
confidence: 99%
“…Las proteínas Yb-1 se unen a la secuencia Yb-1 invertida CCATT (ATTGG) y activan el gen MDR1 que codifica un transportador ABC (ATP-Binding Cassette), que actúa expulsando de las células los compuestos que les resultan tóxicos (por ejemplo, los compuestos antitumorales). En pacientes de cáncer siempre se comprueba si se está sintetizando esta proteína ya que su expresión en células cancerígenas es un indicador de resistencia a tratamientos antitumorales (Nakaminami, 2006). Sin embargo, en herbáceas, esta familia nunca ha sido asociada en respuesta a xenobióticos.…”
Section: Pcsp4 Candidato Fitorremediadorunclassified
“…Las regiones ricas en glicina y los dedos de zinc CCHC están implicados en la unión a ácidos nucléicos y a la unión a otras proteínas (Karlson et al, 2002;Nakaminami et al, 2006;Sasaki et al, 2007). La mayoría de los estudios de esta familia se han centrado a la caracterización de proteínas CSP de bacterias y animales, existiendo en la actualidad poca información sobre de las proteínas CSP en plantas.…”
Section: Análisis Filogenético De La Familia Csp En Plantasunclassified